Zirconia-based materials in alternative energy devices - A strategy for improving material properties by optimizing the characteristics of initial powders. (15th December 2022) - Akhkozov, Leonid; Danilenko, Igor; Podhurska, Viktoriya; Shylo, Artem; Vasyliv, Bogdan; Ostash, Orest; Lyubchyk, Andriy
Abstract: This work is devoted to the demonstration of a real multifunctional material – zirconia based nanopowders, which can be used in the manufacture of various types of devices that convert natural energy sources into electricity (electrolyte and anode for SOFC, moisture-to-electricity converter). It was shown that such characteristics of nanopowders as particle size, specific surface area, and type of surface centers, which depend on the temperature of nanopowder synthesis, could play both a positive and a negative role in the formation of the functional properties of a device. It was found that the synthesis of 8YSZ nanopowders at 700 °C is optimal for the manufacture of a dense electrolyte material and a porous SOFC anode material during sintering at 1400–1450 °C. The addition of a small amount of Al2 O3 at the synthesis stage accelerates the sintering of the SOFC electrolyte material by 120 °C and leads to increasing the density to 97% of the theoretical value. The strength of the sintered anode material practically does not change after reduction in an atmosphere of N2 –10% H2 –5% CO2 and the value is 100 MPa. The synthesis temperature of 8YSZ nanopowder at 700 °C is also optimal for the manufacture of porous converters of ambient humidity into electricity. The formation of particles with a given size and type of surface centers allows generating an electric potential (100–200 mV) for hundreds of hours, which is 2–3 times higher than that of larger and smaller powders. The result of the work show that there are optimal conditions for the synthesis of powders (synthesis method, additives, synthesis temperature), as a result of which nanopowders are formed with characteristics (particle size, specific surface area, morphology) necessary and sufficient for the manufacture of several types of materials for devices of alternative energy. Graphical abstract: Image 1 Highlights: 8YSZ is the universal material for converting ambient energy sources to electricity. Creating a database powder – technology-characteristics - products – properties. Testing during the manufacture of SOFC components and MEG converter. Optimum condition of powder synthesis for the production of SOFC and MEG were found.